2022
DOI: 10.1002/ece3.8856
|View full text |Cite
|
Sign up to set email alerts
|

Causes, temporal trends, and the effects of urbanization on admissions of wild raptors to rehabilitation centers in England and Wales

Abstract: Data from wildlife rehabilitation centers (WRCs) can provide on-the-ground records of causes of raptor morbidity and mortality, allowing threat patterns to be explored throughout time and space. We provide an overview of native raptor admissions to four WRCs in England and Wales, quantifying the main causes of morbidity and mortality, trends over time, and associations between threats and urbanization between 2001 and 2019. Throughout the study period, 14 raptor species were admitted totalling 3305 admission r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 101 publications
4
10
0
Order By: Relevance
“…The low prevalence of infectious disease and toxicosis found in this study could be explained by the presence of multiple morbidity and mortality factors. These results were consistent with similar studies [ 15 , 21 , 24 , 25 , 28 , 56 ] but in contrast with those reported in Morishita et al [ 13 ], who found that 30.3% (124/409) of the examined raptors had infectious or toxic effects. However, in this last study, only dead raptors presented for necropsy were analyzed, so neither nestling nor starvation of birds of prey were considered.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The low prevalence of infectious disease and toxicosis found in this study could be explained by the presence of multiple morbidity and mortality factors. These results were consistent with similar studies [ 15 , 21 , 24 , 25 , 28 , 56 ] but in contrast with those reported in Morishita et al [ 13 ], who found that 30.3% (124/409) of the examined raptors had infectious or toxic effects. However, in this last study, only dead raptors presented for necropsy were analyzed, so neither nestling nor starvation of birds of prey were considered.…”
Section: Discussionsupporting
confidence: 93%
“…It was therefore chosen to keep information on the anatomical location of the trauma and not on its origin. This choice does not allow a full comparison of the origins of the trauma with other published studies; however, it was possible to confirm that the traumatic diagnosis is the main cause of admission for birds of prey in a WRC [ 13 , 14 , 15 , 26 , 27 , 28 , 40 , 44 , 45 , 46 , 47 , 48 ]. These results are, however, in contrast with finding trauma in only 5% of 92 free-living British Kestrels ( Falco tinnunculus ) in another study [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations